Rural Districts Left Behind? Rural Districts and the Challenges of Administering the Elementary and Secondary Education Act - Holy Yettick; Robin Baker; Mary Wickersham; Kelly Hupfeld (Journal of Research in Rural Education, 2014)
The purpose of this study was to inform the upcoming and overdue reauthorization of the Elementary and Secondary Education Act (ESEA) by exploring whether rural school districts face disadvantages as they attempt to follow the law's provisions and, if so, if the law's rural-specifi c section ameliorates these disadvantages. The research drew upon interviews and survey results from rural Colorado as well as from a comparison group of non-rural school districts in the state. The fi ndings suggest that rural districts are indeed uniquely administratively disadvantaged when it comes to the law. However, they also share certain challenges with their non-rural counterparts. The article concludes with policy recommendations that address challenges experienced by districts across the rural-urban continuum as well as challenges that are specifi c to the rural context.